Science@IIUM Issue 3 - Saad, Shahbudin; Mohammad Noor, Normawaty; Zahaba, Maryam; Che Othman, Siti Fairuz; Ahmad, Norfaieqah; Abd Hamid, Khairul Bariyah; Abdul Razak, Rashidah; Ismail, Mohamad Wafiuddin; Isa, Hafizah Noor; Abdullah, Nor Azahana; Mohd Nasir, Mohd Hamzah; Mohd Ikhsan, Amar Muhsin (Kulliyyah of Science, International Islamic University Malaysia, 2020)
Science@IIUM is a magazine that celebrates the members of Kulliyyah of Science, IIUM. Through interviews, image stories and curated content, Science@IIUM highlights the success and anecdotes from those who explore and challenge themselves in academics and also in other areas.